Locus of control: Perceptual study of hotel management students at Nepal Academy of Tourism and Hotel Management (NATHM) - Raut, Raju (SADGAMAYA, 2024)
The study investigated the locus of control in hotel management student of Nepal Academy of Tourism and Hotel Management (NATHM). The study has selected a sample size of hundred individuals to investigate personality traits based on locus of control. Among the hundred students an even number of fifty male and fifty female currently studying at NATHM located in Kathmandu, Nepal has been considered for investigation. The study revealed that most of the students have internal and external locus of control meaning that they believe both internal and external factors as described by Rotters and other studies.